Carotid baroreflex responsiveness in normotensive African Americans is attenuated at rest and during dynamic leg exercise - Holwerda, Seth W.; Samels, Mitchel; Keller, David M. (Frontiers in Physiology, 2013)
Evidence suggests differences between African Americans (AA) and Caucasian Americans (CA) in cardiovascular responsiveness to physiological stressors. This study tested the hypothesis that carotid baroreflex (CBR) control of heart rate (HR) and blood pressure is reduced in AAs compared to CAs during exercise. Mean arterial pressure (MAP) and HR were continuously recorded at rest and during leg cycling in 23 nonhypertensive male subjects (12 AA; 11 CA; age 19-26 yr). CBR control of HR and MAP was assessed with 5-sec pulses of neck pressure (NP, simulated hypotension) and neck suction (NS, simulated hypertension) ranging from +45 to -80 Torr. Across all NS stimuli (-20, -40, -60, -80 Torr) at rest, the AA group demonstrated attenuated CBR-mediated reductions in HR (AA, -8.9 ± 1.9 vs. CA, -14.1 ± 2.3 bpm; P<0.001) and MAP (AA, -6.4 ± 1 vs. CA, -7.8 ± 0.8 mmHg; P<0.05). Despite similar gain and magnitude of resetting observed in the modeled stimulus response curves, an attenuation among AAs persisted in HR (AA, -8.2 ± 1.6 vs. CA, -11.8 ± 3 bpm; P<0.05) and MAP (AA, -6.8 ± 0.9 vs. CA, -8.2 ± 1.1 mmHg; P<0.05) responses to NS during exercise. No differences in CBR-mediated HR and MAP responses to NP were detected between groups at rest or during exercise. These data suggest impairment in the ability to defend against a hypertensive challenge among AAs during steady-state exercise compared to their CA counterparts.